MODERASI BRAND IMAGE DALAM MENENTUKAN KEPUTUSAN PEMBELIAN PADA TOKO THRIFT AW DI SITUBONDO - Norchalicatin, Yuli; Fandiyanto, Randika; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
A company in winning the competition is by carrying out marketing strategies for the products that have been produced. The advantage in competition in the business world is to form a brand image. Thrift AW Store is one of the stores that sells used imported clothing in Situbondo. The purpose of this study was to test and analyze the effect of Brand image in moderating product quality and price on purchasing decisions. The population in this study were consumers of Thrift AW Stores in Situbondo. The sampling technique determined using simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application, show that product quality has a significant positive effect on purchasing decisions, price has a significant positive effect on purchasing decisions, brand image has a positive but insignificant effect in moderating the effect of product quality on purchasing decisions, brand image has a negative but insignificant effect in moderating the effect of price on purchasing decisions.